Ergonomics Informational and Health: a contribution to the study of diabetes (Estudos em Design, 2015)
This article is a study related to the analysis of educational materials for health promotion, concerning the perception of diabetes information. To conduct the research a study was initiated through interviews with patients that led to an online questionnaire creating profiles that should facilitate the production of informational media. The conclusion of this stage, presented here, foster a broader investigation in progress.
Keywords: Diabetes; Pictograms; Persona